Memahami Dosa Dalam Dua Perspektif:Dosa Yang Mendatangkan Maut dan Dosa Yang Tidak Mendatangkan Maut Menurut 1 Yohanes 5:16-17 - ester gulo (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
AbstractOne of the obstacles for humans in obeying God's commands is sin. The act of sin is often times associated with the death of the eternal. So the study 's authors aimed to describe about sin in two perspectives, namely sin that brings death and sin that does not bring death according to 1 John 5:16-17.  Therefore, the sin that is intended by the apostle John is different with the sense of sin that is understood by the people believe when this. Sin that does not incur death is sin which is not required on the death of the eternal. The cause of this sin is the result of carelessness in acting thus rated as a sin which is not expected. Sin that does not lead to the death of this also involves the problem of inner that is not just watchfulness will power of sin. Because of it, to kind of sin is still obtain assurance salvation or life that is eternal of God. It is this that distinguishes the sin is the sin that brings death. With such a sin that brings death is sin that has been rewarded with the death of the eternal as the reward of deeds are done. Sin that brings death characterized by properties that do not have the characteristics of a child of God because actions they lead to the rejection of the gospel who does not walk in the way the truth of Christ. In a study of this, the authors describe it through the method of exegesis to understand the intent in paragraph of this. Besides that, the authors also take some of the material of the interpreters of the Bible and journal are associated with discussion Keywords:  Sin, Death, John, Life, Prayer, Eternal